NILAI-NILAI PENDIDIKAN KARAKTER DALAM PERIBAHASA DOLA BILOLO MASYARAKAT TIDORE - Aisun Jafar; Nurbaya Nurbaya; Sarmina Ati (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This study aims to identify and analyze the character education values ​​contained in the Dola Bilolo proverbs of the Tidore community. The research method used is descriptive qualitative with semantic and anthropological-linguistic approaches. Data were obtained through interviews with traditional leaders and the Tidore community and documentation of the forms of Dola Bilolo that are still used in social life. The results of the study indicate that Dola Bilolo functions as a means of traditional character education that instills moral values ​​such as honesty, responsibility, religiosity, tolerance, and mutual cooperation. These values ​​strengthen individual character and maintain social cohesion in the community. Theoretically, this study shows that proverbs as a form of oral literature can be used as a medium for character education based on local wisdom.